Outcomes of Sutureless Iris-Claw Lens Implantation - Choragiewicz, Tomasz (J Ophthalmol, 2016)
Purpose. To evaluate the indications, refraction, and visual and safety outcomes of iris-claw intraocular lens implanted retropupillary with sutureless technique during primary or secondary operation. Methods. Retrospective study of case series. The Haigis formula was used to calculate intraocular lens power. In all cases the wound was closed without suturing. Results. The study comprised 47 eyes. The mean follow-up time was 15.9 months (SD 12.2). The mean preoperative CDVA was 0.25 (SD 0.21). The final mean CDVA was 0.46 (SD 0.27). No hypotony or need for wound suturing was observed postoperatively. Mean postoperative refractive error was −0.27 Dsph (−3.87 Dsph to +2.85 Dsph; median 0.0, SD 1.28). The mean postoperative astigmatism was −1.82 Dcyl (min −0.25, max −5.5; median −1.25, SD 1.07). Postoperative complications were observed in 10 eyes. The most common complication was ovalization of the iris, which was observed in 8 eyes. The mean operation time was 35.9 min (min 11 min, max 79 min; median 34, SD 15.4). Conclusion. Retropupilary iris-claw intraocular lens (IOL) implantation with sutureless wound closing is an easy and fast method, ensuring good refractive outcome and a low risk of complication. The Haigis formula proved to be predictable in postoperative refraction.